An Overview of Dental Assistants\' educational Status and Performance in Iran - Yasin Baghban; Imaneh Asgari (Babol University of Medical Sciences, 2022)
Introduction: Demanding qualitative dental services calls for hiring competent staff in dental offices. This study was designed to evaluate dental assistants' educational status and ability to perform tasks. Materials & Methods: In this cross-sectional study, 200 dental assistants working in the offices and clinics of Isfahan, Iran during 2020 were selected using random systematic sampling. The researcher-made evaluation tool with a content validity index of 0.77 was used. Tasks were evaluated by 13 items in 6 sub-scales including communication skills, preparation, radiography, cooperation with dentists, health promotion through prevention and infection control. Moreover, information was requested about the education and training course of the dental assistant. The score of ability was achieved at the range of 0 to 20. The relationship between gender and training course as well as between age and experience level was evaluated with Mann-Whitney test and Spearman correlation. Results: The most frequent major of the study was accounting. The mean total ability score of the dental assistants was 19.1±6.5, ranging from 17.7 to 20. The highest and lowest ability scores were related to the cooperation with dentists and health promotion through prevention, respectively. The mean ability score had a weak relationship with age but had no significant relationship with experience. The mean ability score only in the area of radiography had a significant relationship with the training course and gender (P=0.012). Conclusion: Despite the diversity in the degree and field of study, the ability and task status of the assistants was desirable. In the area of health promotion through prevention, there is a need for training and monitoring its implementation.